(untitled) (Journal of Governance and Development (JGD), 2021)
Online food delivery service is a process where the customer can search for the available restaurants and their orders will be delivered based on their locations by the system in the online food delivery application. The usage of online food delivery service among the public has been increasing and it is getting common especially during the pandemic of Covid-19. The user of this online food delivery service included workers, specifically students who are seeking for the conveniences provided by the service because they are busy with their tasks and study most of the time which they are lacking time to dine in the restaurant. The objective of this research is to analyse the level of satisfaction towards online food delivery service, identify the main factors that influence the level of satisfaction and determine the methods to improve the level of satisfaction towards online food delivery service among students in UUM. The population of this research is only concentrated on the students in UUM which contains around 5000 of students. Besides, 350 respondents will be chosen randomly to answer a designated questionnaire regarding online food delivery service. The researcher analysed the data collected using several analysing approaches such as descriptive statistics, Cronbach’s alpha result, correlation analysis and others through Statistical Package Social Science (SPSS). Validity, Reliability and Normality Tests had also been conducted in order to ensure that the data is adequate to be used in the analysis. At the end of the research, the researcher concluded that the major factors are ‘Security’ and ‘Promotion’, and the respondents are mostly satisfied with the online food delivery service.